The Impact of Maternal Social Support on Children's Mental Health Outcomes in Low Income Neighborhoods - Babal, Roshni. (Tufts University. Tisch Library., 2022)
Thesis (M.A.)--Tufts University, 2022.; Submitted to the Dept. of Child Development.; Advisor: Ann Easterbrooks.; Committee: Christine McWayne, and Anat Weisenfreund.; Keyword: Psychology.